Finite-Difference Analysis of Influence of Borehole Diameter and Spacing on Reduction in Rockburst Potential of Burst-Prone Coal Seams - Mikhail O. Eremin; Artyom O. Chirkov; Albert Pazhin; Sergey A. Laptev; Dmitriy V. Chanov (Mining)
Decreasing the rockburst potential in longwall mining of burst-prone coal seams has been a longstanding challenge for geotechnical engineering worldwide. One of the effective approaches is drilling of relief boreholes in front of the coal seam face from the airways. This work presents a novel approach based on the integral rockburst factor (<semantics>KIrb</semantics>) taking account of the length of the dynamic abutment stress influence zone and the ratio of the vertical stress to the remote field virgin stress. The geotechnical conditions of seam 3 of the Alardinskaya mine (Kuznetsky basin, Russia) are taken as a study site. An approach of the finite-difference continuum damage mechanics is employed to describe the processes of deformation and fracture of coal and host rocks using an in-house software. The results indicate that the abutment stress maximum shifts deep into the seam after drilling and that the stress distribution along the coal seam horizon is a superposition of the solutions similar to those of the elastoplastic Kirsch problem. The results also indicate that the curves of <semantics>KIrb</semantics> dependence on spacing between the boreholes and their diameter are nonlinear and non-monotonic functions, which allows for optimizing of the drilling technology.